Investigating Item Invariance in Geography Essay Questions of West African Senior Certificate Examinations for Nigerian Candidates - Idris Mohammed Jimoh; Rashidat Omotayo Abdulsalam-Nuhu; Rasaq Sulyman (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2024)
The distinctive feature of test items in an instrument is its quality that brings about fairness, consistency, and reliability. The study, therefore, examined item invariance in geography essay questions for Nigerian candidates in West African Senior Certificate Examinations across gender and school location The design was descriptive survey. The population comprised Senior geography students attending senior secondary schools 1, 2 and 3, while the target population included Senior Secondary School students 3 who registered 2020–2021 academic session across Nigeria. Multiphase sampling process involving stratified, proportionate, purposive, and simple random sampling techniques were considered. The sample size was 1,546 examinees. The 2019 2020 West African Senior Certificate Examinations essay questions on the physical and practical geography component, paper 3 were chosen as the research tool. The research questions raised were answered using line graphs. It was concluded that WASSCE 2019/2020 physical geography paper 3 items were invariance based on gender, while they were at variance based on the school location. It was suggested that education stakeholders collaborate in addressing the issues of rural-urban disparities in terms of better access to educational resources.